Cytotoxic potential of Nephthea sp.-derived actinomycetes supported by metabolomics analysis. Issue 24 (17th December 2022) - Abdelhafez, Omnia Hesham; Fahim, John Refaat; Rateb, Mostafa E.; Ngwa, Che J.; Pradel, Gabriele; Abdelmohsen, Usama Ramadan; Desoukey, Samar Yehia; Kamel, Mohamed Salah
Abstract: Soft corals and associated microorganisms are known to produce leads for anticancer drugs. Keeping this in mind, Nephthea sp.; a Red Sea soft coral was investigated for the first time using the OSMAC approach. Two isolates, Streptomyces sp. UR63 and Micrococcus sp. UR67 were identified. Their extracts revealed the presence of alkaloids, macrolides, quinones, fatty acids and terpenoids. Further comparison through a set of multivariate data analyses revealed their unique chemical profiles. The extracts displayed inhibitory potencies against HepG-2, Caco-2 and MCF-7 tumor cell lines with IC50 values ranging from 11.4 to 38.7 μg/mL when compared with the positive control, doxorubicin. The study not only highlights the cytotoxic potential of soft coral-associated actinomycetes but also shows the advantage of using the OSMAC approach in this regard. Graphical Abstract: UF0001